2020
DOI: 10.57046/xewv4118
|View full text |Cite
|
Sign up to set email alerts
|

Food habit and ecological balance of fish species in Osun river, Nigeria

Abstract: The food habit and ecological balance of fish species in Osun River were investigated for a period of 12 months (November 2017 to October 2018) with monthly sampling of water and fish species in the river. Fish were sampled using monofilament gill nets of mesh size between 25mm and 101mm. A total of 4544 individuals belonging to 19 species and 10 families were captured. They were grouped based on their feeding habits into herbivores, carnivores, and omnivores. Carnivores dominated the River (38.63%) with Cichl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…These values indicated that the dissolved oxygen concentration in the reservoir is tolerable for fish survival. Similar values were reported in Eleyele Reservoir [39] and Osun River [40]. These mean pH values recorded across the zones (7.00±0.00) and overall mean (7.00 ± 0.00) were within the range of 6.5 -9 as stated by USEPA [35].…”
Section: Water Qualitysupporting
confidence: 87%
See 3 more Smart Citations
“…These values indicated that the dissolved oxygen concentration in the reservoir is tolerable for fish survival. Similar values were reported in Eleyele Reservoir [39] and Osun River [40]. These mean pH values recorded across the zones (7.00±0.00) and overall mean (7.00 ± 0.00) were within the range of 6.5 -9 as stated by USEPA [35].…”
Section: Water Qualitysupporting
confidence: 87%
“…Simpson's index was highest in May and least in September which indicated a low and high diversity, respectively. As stated by Shannon and Weiner [40], the higher the fish abundance the lower the diversity and vice versa. The Shannon diversity indices had most of the calculated values across the months higher than 1, which indicated a fairly high diversity of fish species across the months of study.…”
Section: Fish Distributionmentioning
confidence: 89%
See 2 more Smart Citations
“…Thereby, values of F/C ratio obtained in Kossou and Taabo lakes (respectively 0.87 and 1.28) fell outside the expected range. This indicated the unsuitable ecological balance between carnivores and their prey populations in Kossou and Taabo lakes (Iyiola et al, 2020). The pressure of fishing evocated by Blé (2008) and Diarra (2020) could explain this situation.…”
Section: Ecological Balancementioning
confidence: 99%